2021
DOI: 10.3390/molecules26061744
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis Methodology of PEGylated Fe3O4@Ag Nanoparticles Supported by Their Physicochemical Evaluation

Abstract: Many investigations are currently being performed to develop the effective synthesis methodology of magnetic nanoparticles with appropriately functionalized surfaces. Here, the novelty of the presented work involves the preparation of nano-sized PEGylated Fe3O4@Ag particles, i.e., the main purpose was the synthesis of magnetic nanoparticles with a functionalized surface. Firstly, Fe3O4 particles were prepared via the Massart process. Next, Ag+ reduction was conducted in the presence of Fe3O4 particles to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
1
4
1
Order By: Relevance
“…The zeta potential value shows that the nanoparticles are almost electrically neutral, and the stability of the nanoparticles in solution is relatively good [16]. The results are quite similar to Kędzierska's study in 2021 [17].…”
Section: Discussionsupporting
confidence: 84%
“…The zeta potential value shows that the nanoparticles are almost electrically neutral, and the stability of the nanoparticles in solution is relatively good [16]. The results are quite similar to Kędzierska's study in 2021 [17].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, when the ζ-potential of the nanoparticles shows a higher absolute value, these have lower tendency to aggregate. In Kędzierska et al's work 35 , MNPs' ζ-potential in aqueous medium was reported to be -15.63 mV, which, in absolute terms, is lower than the one obtained for the ones we formulated, indicating an improved stability in solution of the MNPs in the present work. Using the same coprecipitation fabrication method, Darwish et al 36 obtained MNPs with a ζ-potential comparable to the one obtained in this work, of 36.9 mV.…”
Section: Mnps Characterizationcontrasting
confidence: 68%
“…Synthesis was performed using Fe 3 O 4 magnetic nanoparticles that were previously obtained via Massart synthesis. This procedure was described in detail by Kędzierska et al [22]. In order to prepare Fe 3 O 4 @Ag nanoparticles, 7.50 mL of an iron oxide nanoparticle suspension was added to an aqueous Arabic gum solution; the solution of this stabilizer was prepared with various concentrations, i.e., 1.0% and 3.0%.…”
Section: The Synthesis Methodology For Fe 3 O 4 @Ag Nanoparticlesmentioning
confidence: 99%